The Bible as a Product of Cultural Power: The Case of Gender Ideology in the English Standard Version. (21st October 2019) - Perry, Samuel L
Abstract: Sociologists whose research intersects with American Christianity recognize the critical importance of the Bible to understanding many Americans' beliefs, values, and behaviors, but their operative approach to the Bible generally ignores that "the Bible" is as much a product of interpretive communities as it is a symbolic marker of identity or shaper of social life. I propose that rather than approaching "the Bible" through a distinctly Protestant lens, as given―specifically as uniform, static, and exogenous―sociologists should apply a critical lens to re-conceptualize the Bible more accurately. That is, sociologists should recognize that Bibles are multiform; they are dynamic; and their contents (not just their current interpretations) are highly contingent on temporal culture and power, being the product of manipulation by interpretive communities and actors with vested interests. Using a recent case study of how complementarian gender ideology became systematically inserted into one the most popular English Bible translations among evangelicals today, I illustrate how a more critical approach toward "the Bible" can provide richer, more sophisticated sociological analyses of power and cultural reproduction within Christian traditions.